2021
DOI: 10.1111/jfpp.15619
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory properties of gluten‐free cupcakes added with fig seeds pomace flour

Abstract: Gluten-free cupcakes were supplemented by different ratios of fig seeds pomace flour (FSF) (100/0, 90/10, 70/30, and 50/50) to improve product quality while reducing the glycemic index.Moisture content, browning index, specific volume, porosity, color, and textural properties of gluten-free cupcakes were investigated. Estimated glycemic index by in vitro digestion, total phenolic content, antioxidant activity, and cupcakes' sensory properties were also evaluated. The cupcakes with FSF, having glycemic index lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This increase is thought to be associated with caramelization or Maillard reactions forming dark brown components. In numerous studies, changes occurring in bakery products produced using different seed flours have been attributed to Maillard reactions [ 9 , 11 , 28 , 29 , 30 ]. Similarly, the b* values of the inner and outer surfaces of baton cake samples ranged from 18.57 to 25.58 and 24.22 to 32.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase is thought to be associated with caramelization or Maillard reactions forming dark brown components. In numerous studies, changes occurring in bakery products produced using different seed flours have been attributed to Maillard reactions [ 9 , 11 , 28 , 29 , 30 ]. Similarly, the b* values of the inner and outer surfaces of baton cake samples ranged from 18.57 to 25.58 and 24.22 to 32.39, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by Ertaş and Aslan (2020) indicated a decrease in moisture content in cookie samples where wheat flour was substituted with hemp flour in varying proportions [ 37 ]. The moisture content of the control sample produced with rice flour was higher compared to other samples, likely due to the high starch content of rice flour retaining water [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the partial use of the peeled fruit by the confectionary industry leads to the generation of fig peel, a by-product that could represent an interesting source of anthocyanins and colorless (poly)phenols. Indeed, previous studies on fig-derived (poly)phenols discovered that these compounds are mainly located in the skin rather than the pulp [7][8][9][10][11][12][13], thus making the skin potentially reusable by the food industry to develop functional foods with increased (poly)phenol content, as recently proposed for fig seeds [14].…”
Section: Introductionmentioning
confidence: 94%